The status of RNAi-based transgenic research in plant nematology - Dutta, Tushar K.; Banakar, Prakash; Rao, Uma (Frontiers in Microbiology, 2015)
With the understanding of nematode-plant interactions at the molecular level, new avenues for engineering resistance have opened up, with RNA interference being one of them. Induction of RNAi by delivering double-stranded RNA (dsRNA) has been very successful in the model non-parasitic nematode, Caenorhabditis elegans, while in plant nematodes, dsRNA delivery has been accomplished by soaking nematodes with dsRNA solution mixed with synthetic neurostimulants. The success of in vitro RNAi of target genes has inspired the use of in planta delivery of dsRNA to feeding nematodes. The most convincing success of host-delivered RNAi has been achieved against root-knot nematodes. Plant-mediated RNAi has been shown to lead to the specific down-regulation of target genes in invading nematodes, which had a profound effect on nematode development. RNAi-based transgenics are advantageous as they do not produce any functional foreign proteins and target organisms in a sequence-specific manner. Although the development of RNAi-based transgenics against plant nematodes is still in the preliminary stage, they offer novel management strategy for the future.